1996
DOI: 10.1093/clinids/22.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Lung Abscess in Patients with AIDS

Abstract: We identified 31 patients with human immunodeficiency virus (HIV) infection and lung abscess. All patients had advanced HIV disease, and the mean CD4 cell count was 17/mm3 (range, 2-50/mm3). Twenty-two patients (71%) had previous opportunistic infections, and 24 (77%) had previous pulmonary infections. Symptoms at the time of presentation included fever (90% of patients), cough (87%), dyspnea (35%), pleuritic chest pain (26%), and hemoptysis (10%). The microbiological etiology was established for 28 patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In the cohort study of GILKS et al [10], a first episode of bacterial pneumonia was observed in 54 patients during a 36-month follow-up. During this relatively short follow-up period, a first recurrence of bacterial pneumonia occurred in 24% of cases, which is the very high recurrence rate usually reported for HIV-infected patients [22,28,69,76]. The recurrence might be due to the same or a new pathogen [80].…”
Section: Course Of Bacterial Lower Respiratory Tract Infectionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the cohort study of GILKS et al [10], a first episode of bacterial pneumonia was observed in 54 patients during a 36-month follow-up. During this relatively short follow-up period, a first recurrence of bacterial pneumonia occurred in 24% of cases, which is the very high recurrence rate usually reported for HIV-infected patients [22,28,69,76]. The recurrence might be due to the same or a new pathogen [80].…”
Section: Course Of Bacterial Lower Respiratory Tract Infectionmentioning
confidence: 73%
“…The third situation with subacute or moderate progression of the condition, fever, weight loss, nodules [75] or alveolar infiltrates, with or without cavitation [76], in a patient with a CD4 T-cell count of v100 cells?mm -3 , usually indicates an opportunistic infection due to mycobacteria, fungus, Nocardia spp. or R. equi, but S. aureus, members of the Enterobacteriaceae family or P. aeruginosa might also be responsible.…”
Section: Clinical Presentation and Diagnostic Management Of Lower Resmentioning
confidence: 99%
“…Although cavitating lung nodules have been described in pulmonary cryptococcosis, presentation with lung abscesses due to Cryptococcus is extremely rare. We came across only four cases of cryptococcal lung abscess reported in the published literature 2 3 22 23. Empyema due to Cryptococcus infection is also rare, with only a few reports both in HIV-infected and non-HIV-infected patients with other immunocompromising conditions 24 25.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary cryptococcosis can present as nodules or mass-like lesions. There have been few reports of cryptococcal lung abscess 2 3. We describe an apparently immunocompetent patient who presented to us initially with a lung mass that progressed to lung abscess and empyema, and was diagnosed as disseminated cryptococcal disease.…”
Section: Introductionmentioning
confidence: 92%
“…Pseudomonas aeruginosa is a known cause of lung abscess in immune compromised hosts and other special populations such as injection drug users . However, the ability of this organism to persist in an otherwise quiescent lung nodule and recrudesce into an active infection is not generally appreciated or well documented.…”
mentioning
confidence: 99%